The geographical dimension of income and consumption inequality: Evidence from the Attica Metropolitan Region of Greece - Yannis Psycharis; Thomas Georgiadis; Panagiotis Nikolopoulos (REGION, 2023)
This paper aims at examining interpersonal income and consumption inequality within the Attica Metropolitan Region, which includes Athens, the largest metropolis of Greece. It also aims to make comparisons between Attica and the rest of the country. The analysis is based on income and consumption microdata from Greek Household Budget Surveys (HBS) over the period 2008-2019, encapsulating the period from the commencement of the economic crisis until the year before the outset of the COVID-19 pandemic. Results indicate that income inequalities are systematically higher than consumption inequalities. From a spatial comparative perspective, the results show that the Attica Metropolitan Region exhibits a higher degree of income and consumption inequality relative to the rest of the country. Furthermore, the economic crisis increased income inequality in Athens and in the rest of the country, while consumption expenditure inequality increased in the Athens metropolitan area only. Finally, the distance between socio-economic groups, which stands as a measure of the degree of social polarization, increased during the economic crisis. However, this does not hold true for consumption inequality. Overall, the analysis demonstrates the sensitivity of inequality outcomes to the selection of the welfare indicator (income or consumption), as well as a number of noticeable differences in inequality outcomes between the Metropolitan region of Attica and the rest of the country. The paper unveils facets of inequality which necessitate the implementation of more people and place-targeted policies aimed at more inclusive and balanced welfare conditions in metropolitan regions and across the country.
Keywords: P25; R58; D31; D63; O15; 330; income inequality; consumption inequality; intra-regional inequality; urban inequality; Athens; Metropolitan Region of Attica